2012
DOI: 10.1155/2012/928187
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Maternal Immunity to Newborns of Diabetic Mothers

Abstract: This study was carried out with hyperglycemic pregnant women to investigate the transfer of antibody classes to newborns across the placenta or by colostrum and the functional activity of phagocytes in maternal blood, cord blood, and colostrum from diabetes mothers. Samples from maternal blood, cord blood, and colostrum were collected from 20 normoglycemic and 20 hyperglycemic pregnant women. We determined antibodies levels, superoxide release, phagocytosis and bactericidal activity of phagocytes. We demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 38 publications
3
41
0
1
Order By: Relevance
“…Phagocytic disorders are in fact the major cause of infectious diseases, especially bacterial infections (Larijani et al 2007). The phagocytic and bacterial activity of cord blood mononuclear phagocytes against enteropathogenic Escherichia coli (EPEC) is low in pregnant women with hyperglycemia (França et al 2012). These evidences reinforce our findings on the decrease in HSP70 levels in offspring from rats with mild diabetes, which can be associated with decrease in the immune response observed in offspring from hyperglycemic dams.…”
Section: Discussionsupporting
confidence: 83%
“…Phagocytic disorders are in fact the major cause of infectious diseases, especially bacterial infections (Larijani et al 2007). The phagocytic and bacterial activity of cord blood mononuclear phagocytes against enteropathogenic Escherichia coli (EPEC) is low in pregnant women with hyperglycemia (França et al 2012). These evidences reinforce our findings on the decrease in HSP70 levels in offspring from rats with mild diabetes, which can be associated with decrease in the immune response observed in offspring from hyperglycemic dams.…”
Section: Discussionsupporting
confidence: 83%
“…Studies suggest that maternal characteristics can cause variations in the components of colostrum and milk, and these changes are dependent on the nutritional status or previous diseases of the mother (Olivares et al 2007;Teixeira et al 2010;França et al 2011aFrança et al , 2012aFrança et al , 2013Morceli et al 2011Morceli et al , 2013. This work shows the influence of maternal hypertension on proteins in milk.…”
Section: Discussionmentioning
confidence: 65%
“…The relationship between breastfeeding and the development of several chronic diseases, including obesity, diabetes and hypertension, has been studied (Taylor et al 2005;França et al 2011França et al , 2012aMorceli et al 2011Morceli et al , 2013. Breastfeeding reduces the incidence of acute illness and likely decreases the risk of numerous chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, colostrum from women diagnosed with type 2 diabetes has 30 % lower concentrations of IgA, IgG, and complement C3 protein compared to colostrum obtained from normoglycemic women [105,106]. Glycomic profiling using nano-HPLC chip/TOF MS + multivariate modeling by showed that total abundances for HMO and HMO composition did not vary in breast milk between women with and without gestational diabetes mellitus (GDM), but that the total protein and composition of oligosaccharides N-linked to sIgA and lactoferrin were significantly different [107].…”
Section: Breast Milk Proteins and Protection From Pathogensmentioning
confidence: 99%